An Academic Analysis of Students’ Abstract Thinking Skills through the Implementation of Augmented Reality in Chemical Bonding Instruction - Kurniawati, Yenni; Hartati, Yuli; Fatisa, Yuni; Yenti, Elvi; Maharani, Risma (UIN Fatmawati Sukarno Bengkulu, 2026)
Abstract thinking skills are essential for understanding microscopic concepts in chemistry, particularly in topics such as chemical bonding. This study investigates the effectiveness of augmented reality (AR) as an innovative instructional medium that enhances students’ abstract thinking abilities within the context of chemical bonding. A mixed-method approach with a sequential explanatory design was employed, beginning with a quantitative phase followed by qualitative analysis. The participants were tenth-grade students at one of Madrasah Aliyah Negeri Pekanbaru, selected through purposive sampling. Data were collected using essay-based assessments, semi-structured interviews, and document analysis. The quantitative findings indicate a statistically significant improvement in the abstract thinking skills of students in the experimental group compared to the control group (p = 0.001), with 73.7% of students in the experimental group showing marked progress. Qualitative data further support these results, highlighting that AR facilitated students’ abilities in structural representation, abstraction, and metacognitive awareness. Additionally, AR increased student motivation and deeper engagement with the learning material. These findings suggest that integrating AR in chemistry instruction can be an effective pedagogical strategy to promote the development of abstract reasoning and 21st-century competencies.